2022
DOI: 10.3389/fphar.2022.796336
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender, Body Mass Index, and Age on the Pharmacokinetics of Itraconazole in Healthy Subjects: Non-Compartmental Versus Compartmental Analysis

Abstract: Itraconazole is a triazole antifungal agent with highly variable pharmacokinetics, with not yet fully identified factors as the source of this variability. Our study aimed to examine the influence of body mass index, gender, and age on the first dose pharmacokinetics of itraconazole in healthy subjects, using pharmacokinetic modeling, non-compartmental versus compartmental ones. A total of 114 itraconazole and hydroxy-itraconazole sets of plasma concentrations of healthy subjects of both genders, determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Moreover, the compliance of the participants for itraconazole administration can be confirmed by measuring itraconazole and its metabolite (hydroxy-itraconazole) in plasma. 29 Larger volume of distribution (V d /F) of mitragynine than 7OH (521.1 L vs 23.01 L) in this study should be due to the difference in lipophilicity of the compounds. Manda et al have reported the permeability in epithelial cell for mitragynine, which was 1.45−1.50 times higher than that of 7OH.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Moreover, the compliance of the participants for itraconazole administration can be confirmed by measuring itraconazole and its metabolite (hydroxy-itraconazole) in plasma. 29 Larger volume of distribution (V d /F) of mitragynine than 7OH (521.1 L vs 23.01 L) in this study should be due to the difference in lipophilicity of the compounds. Manda et al have reported the permeability in epithelial cell for mitragynine, which was 1.45−1.50 times higher than that of 7OH.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…29 In females, there was significant reduction of C max and AUC, and increment of V d of itraconazole and hydroxy-itraconazole, compared with males. 29 Given unequal numbers of males and females in our study, i.e., 5 males and 11 females, less exposure to itraconazole in females than in males could occur. This might contribute to the variation for the degree of CYP3A4 inhibition following itraconazole pretreatment.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 3 more Smart Citations